Revisiting the Gwangju Incident and the Dynamics of Democracy in South Korea - Nuangjamnong, Nithi (Journal of Social Sciences Naresuan University, 2025)
This article reassesses the existing studies on the relationship between the 1980 Gwangju Incident and democracy in South Korea. It is publicly assumed that the Gwangju Incident was important to South Korea’s transition to democracy in 1987. However, there are only a few works studying the connection between the Gwangju Incident and the dynamics of democracy in South Korea, which cover both the democratic transition in 1987 and democratic consolidation after 1987 until now. By employing the ‘transformative event’ concept, this article demonstrates the effect of the Gwangju Incident on democratization in South Korea in two aspects. First, the Gwangju Incident has imprinted the ‘original sin’ in the mind of the army, which in turn limits the choice of using force to oppress democratic movements. This first dimension is an enabling factor in the success of the democratic movement in 1987. Second, it creates a ‘generational memory’ and ‘moral obligation’ to address past injustices. Hence, the public has converted this grievance into incessant political movements calling for the establishment of ‘transitional justice’. This second aspect is instrumental in the consolidation of democracy.